Implementation of Profile Matching Method to Determine the Performance Evaluation of the Best Information Systems Lecturer at Prima Indonesia University: Implementation of Profile Matching Method to Determine the Performance Evaluation of the Best Information Systems Lecturer at Prima Indonesia University - Muhardi Saputra; Siti Aisyah; Muhammad Syahputra Novelan; Jacky Lius (Institute of Computer Science (IOCS), 2020)
For each agency, the quality of human resources is one of the main needs that determines the progress and success of the agency. To determine the quality of its human resources, the agency conducts a performance appraisal process. Problems that occur in the process of evaluating the performance of lecturers at the university are still carried out conventionally, the number of evaluation criteria and the need for a long time to complete the performance evaluation of the lecturer. Based on the above problems, the writer tries to provide a solution by designing a decision support system in evaluating lecturer performance using the profile matching method. In this SPK, lecturer performance evaluation is based on five criteria as a reference in decision making. The final result of this study is the value of evaluating the performance of lecturers in carrying out their duties based on assessment for 2 years.